On ξa-quadratic stochastic operators and their classifications - Mukhamedov, Farrukh; Wan Rozali, Wan Nur Fairuz Alwani (Universiti Teknologi MARA, Pulau Pinang, MALAYSIA, 2010)
We introduce a new class of quadratic stochastic operators (QSO) which is called aξ-QSO. In two dimensional simplex, we classify such operators into two non-isomorphic classes